EFFECT OF BURNING CYCLES ON THE PHYSICAL PROPERTIES OF CLAY - Safa Hussain Abid Awn; Waad Abdul Sattar Hussain; Hassan Obaid Abbas (Journal of Engineering and Sustainable Development, 2019)
Natural soil is exposed, like other elements of the construction, to significant changes in temperatures are sources of forest fires or volcanic eruptions or natural bulky. Usually, accompanied by significant changes in temperatures of up to more than 300 degrees centigrade. Therefore, the need arises to study the effect of burning clayey soils, on the grain distribution and distribution of particleboard intricacies and atterbering limit and soil classification, in addition to the direct impact on the variables for the design of foundations such as the cohesion of the soil. The soil used was naturally clayey soil brought from Diyala province with (Liquid limit=56%, Plastic limit=51%, Specific gravity=2.59, the soil is classified as OH (Organic clays of medium to high plasticity). The soil was burned at different temperatures (75- 150- 300- 600°C) using special oven for burning at high temperature, the study was directed to investigate the effect of repeat arson for each grade and study changes in soil properties and distribution particleboard and suitability of the construction. The study showed basic change in the particle distribution and Atterbering limits which means changing the engineering properties for the design of foundations construction which indicates the importance of this types of research and potential development to expand in this area and develop ways to put construction solutions for such cases. A reduction percent in plastic limit was 20% and 26% at the end of the fourth cycle at 300oC and 150oC, respectively.